Minute litter bugs (Heteroptera: Schizopteridae) from the Brazilian Amazon savannas, a poorly sampled biome - Albuquerque, Flavio; De-Souza, Caroline Costa; Favacho, César Augusto Chaves; Carvalho-Filho, Fernando Da Silva (Zootaxa, 2021)
The minute litter bugs (Heteroptera: Schizopteridae) fauna from the Brazilian Amazon comprises only nine species described during the past four years. In this paper, the Schizopteridae fauna of an Amazonian savanna was surveyed, resulting in the discovery of two new species of Corixidea Reuter and a new species of Schizoptera (Cantharocoris) McAtee & Malloch: Corixidea graziae sp. nov., Corixidea quilombola sp. nov., and Schizoptera (Cantharocoris) savannensis sp. nov. The species C. graziae sp. nov. and C. quilombola sp. nov. can be distinguished from other Corixidea species by the shape of the process of mediotergite 8 while S. (Cantharocoris) savannensis sp. nov. can be recognized among species of its subgenus by a combination of the shape of the subgenital plate and right conjunctival appendage. The species herein described represent the first records of these genera for the Brazilian Amazon. We provide diagnoses, photographs of habitus, and illustrations of male genitalia.